An adult case of human parvovirus B19 infection developed ACPA-positive rheumatoid arthritis. (2nd January 2019) - Tono, Toshihiro; Hosoda, Tomohiro; Nagata, Ryohei; Kawaai, Satoshi; Hazue, Ryo; Murota, Atsuko; Taguchi, Hiroaki; Sakamoto, Mitsuo; Ohsone, Yasuo; Okano, Yutaka
Abstract: We report a case of rheumatoid arthritis (RA) developing after parvovirus B19 infection. A 30-year-old Japanese woman, who had no significant medical history admitted for tender erythema in the bilateral upper limbs with progressive polyarthralgia. Serological test showed elevation of serum IgM antibodies for parvovirus B19. Serum anti-cyclic citrullinated peptide antibody (ACPA) and RF were increased at 95.8 U/mL (normal, ≤4.4 U/mL) and 22 IU/mL (normal, ≤15 IU/mL). Radiographs of the hand showed no narrowing of the joint space or bone erosion. Although the erythema of both upper limbs disappeared, polyarthritis persisted. Because C-reactive protein (CRP) and ACPA and RF showed an upward trend, RA was diagnosed together with clinical symptoms. Oral methotrexate was begun at 8 mg/week. Joint pain was alleviated after 1 month, synovitis disappeared after 2 months, and CRP and MMP3 values were negative after 3 months. This case seems to be very rare case which reported a direct relationship between human parvovirus B19 infection and ACPA-positive RA.